Association between Nutritional Awareness and Diet Quality: Evidence from the Observation of Cardiovascular Risk Factors in Luxembourg (ORISCAV-LUX) Study - Alkerwi, Ala'a; Sauvageot, Nicolas; Malan, Leoné; Shivappa, Nitin; Hébert, James (Nutrients, 2015)
This study examined the association between nutritional awareness and diet quality, as indicated by energy density, dietary diversity and adequacy to achieve dietary recommendations, while considering the potentially important role of socioeconomic status (SES). Data were derived from 1351 subjects, aged 18–69 years and enrolled in the ORISCAV-LUX study. Energy density score (EDS), dietary diversity score (DDS) and Recommendation Compliance Index (RCI) were calculated based on data derived from a food frequency questionnaire. Nutritional awareness was defined as self-perception of the importance assigned to eating balanced meals, and classified as high, moderate, or of little importance. Initially, a General Linear Model was fit that adjusted for age, sex, country of birth, and body mass index (BMI). Furthermore, simultaneous contributions to diet quality of individual-level socioeconomic factors, education, and household income were examined across levels of nutritional awareness. Attributing high importance was associated inversely with energy density (p = 0.02), positively with both dietary diversity (p < 0.0001), and adequacy to dietary recommendations (p < 0.0001), independent of demographic factors, weight status and SES. Further adjustment for household income in the EDS-related multivariable model, reduced the β coefficient by 47% for the “moderate importance” category and 36% for the “high importance” category. Likewise, the β coefficient decreased by 13.6% and 10.7% in the DDS-related model, and by 12.5%, and 7.1% in the RCI-related model, respectively, across awareness categories. Nutritional awareness has a direct effect on diet quality, with a minor component of variance explained by improved income. The impact of nutritional awareness on diet quality seems to be a promising area for both health promotion and health policy research.